‘The Comforts of Married Life’: Metis Family Life, Labour, and the Hudson’s Bay Company - Macdougall, Brenda (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2008)
Abstract Since the s, scholars have sought to understand how the Canadian fur trade shaped the Metis. Less attention has been paid to the impact of Metis concepts of family and community on the nature of their relationship with their employer, the Hudson’s Bay Company (hbc). This article focuses on how Metis family structures in the English River District molded the contours of the community’s relationship with the hbc in the 19th century. More specifically, only certain families established a relationship with the Company, wherein male servants and their extended families laboured for the hbc in return for wages and/or access to Company resources. The Company’s willingness to participate in these types of exchanges with its employees’ families cultivated an intergenerational loyalty amongst those Metis, as successive generations were employed by the Company and, in turn, drew upon it as part of their economic resource network. Still, Company oﬃcials faced a dilemma. They recognized that these extended families were loyal contributors to the Company’s trading successes, but likewise regarded them as burdensome and a drain on precious resources. Throughout the 19th century, the ambivalence of the Company grew, negatively impacting its relationship with once loyal hbc servants and their families. The loyalty of families to the Company was only as strong as its loyalty to them. By the end of the century, as the Company’s focus turned to reducing its obligations to families, Metis loyalties also shifted to competing economic ventures, thereby threatening the hbc monopoly in the region.